Organising a Negotiating Team - Kozina, Andrzej (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The objective of the paper is to systematise the most important problems connected with organising a team representing a company within different types of negotiations (either internal or external ones) as well as to present the principles (recommendations, indications and rules) for solving such problems. Creating a negotiating team constitutes one of the most important activities performed within the process of negotiation planning in a company. The following problems concerning the organisation of a negotiating team are described along with the principles for solving those problems: 1) making decisions on appointing a negotiating team, 2) selecting its organisational form, 3) determining its size, 4) stating criteria for selecting members, 5) designating team roles, 6) assigning tasks and their division between team members, 7) delegating decision-making powers.